Comparison of Prefixes and Reduplication of Gorontalo Language and Atinggola Language - Ome, Aas; N. Djou, Dakia; Salam, Salam (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the comparative form and function of prefixes and reduplication in Gorontalo and Atinggola languages using a comparative linguistics approach. This comparison aims to identify similarities and differences in morphological structure in both languages. Data were collected through interviews, observation, and documentation involving native speakers in Randangan District, Pohuwato Regency, and Atinggola District, North Gorontalo Regency. A total of 200 basic Swadesh vocabulary items were used as the primary analysis material. The research findings indicate that both languages have relatively similar morphological systems, particularly in the use of bound morphemes, such as prefixes, which contribute to verb formation. However, there are differences in their productivity and grammatical functions. Gorontalo has six types of prefixes and 20 forms of reduplication, while Atinggola has four types of prefixes and 25 forms of reduplication. Reduplication in both languages serves to express meaning, such as emphasizing intensity, adding meaning, and varying meaning. In general, this research contributes to the development of comparative historical linguistic studies and can be used as a reference in the conservation and development of regional languages in Indonesia.